Carbon-based iron-nitrogen composite material, preparation method and application thereof, and lithium-ion battery
By using carbon-based iron-nitrogen composite material as the negative electrode active material of lithium-ion batteries, the problems of low gram capacity and poor cycle stability of lithium-ion batteries are solved, and higher battery capacity and longer cycle life are achieved.
Patent Information
- Application Number
- CN202411941715.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-26
- Publication Date
- 2025-04-01
AI Technical Summary
Lithium-ion batteries have problems such as low gram capacity, poor cycle stability and poor battery life due to negative electrode active materials.
A carbon-based iron-nitrogen composite material is used as the negative electrode active material of lithium-ion batteries. The iron-containing complex is generated through self-assembly and coordinated reactions of nitrogen-containing ligands and ferrous salts, and a carbon-based iron-nitrogen composite material is obtained by drying and calcining. The material has a layered structure and a hollow tubular particle structure, which improves the migration ability of lithium ions and the cycling stability of the battery.
It significantly improves the gram capacity and cycle stability of lithium-ion batteries, extends the cycle life of the battery, and can meet the needs of long-term applications.
Smart Images

Figure CN119742348A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium ion batteries, and in particular to a carbon-based iron-nitrogen composite material, a preparation method and application thereof, and a lithium ion battery. Background Art
[0002] In recent years, with the surge in global demand for renewable energy and the improvement of environmental awareness, the new energy industry is booming at an unprecedented rate. Among them, lithium-ion batteries (LIBs) play a core role in two major fields: electric vehicles (EVs) and large-scale energy storage systems (ESS) due to their advantages such as high energy density, long cycle life and no memory effect. The widespread application of power batteries and energy storage batteries has not only promoted the popularization of electric vehicles, but also supported the efficient and stable operation of the power grid, becoming one of the key technologies for the transformation of new energy.
[0003] However, it is difficult to improve the energy density of lithium-ion battery performance, which has long been a common problem faced by scientific research and industry. As an important component of battery performance, the selection of negative electrode materials is crucial to improving the overall energy density and cycle stability of the battery. The theoretical gram capacity of traditional graphite negative electrode materials is 372mAh / g, but due to the limitations of the charging and discharging process in practical applications, its actual gram capacity is often lower than 360mAh / g, and traditional graphite negative electrode materials have the problem of volume expansion during the cycle process, which will affect the capacity and cycle stability of the battery. This shortcoming limits its application in long-cycle batteries.
[0004] In view of the above problems, there is an urgent need to develop a new type of negative electrode material, which can not only provide high capacity but also have excellent cycle stability to meet the needs of long-term application of lithium-ion batteries. Summary of the invention
[0005] The main purpose of the present invention is to provide a carbon-based iron-nitrogen composite material, a preparation method and application thereof, and a lithium-ion battery, so as to solve the problems of low gram capacity and poor cycle stability of lithium-ion batteries caused by negative electrode active materials in the prior art, as well as poor endurance of lithium-ion batteries caused by the negative electrode active materials.
[0006] In order to solve the above problems, the present invention provides a method for preparing a carbon-based iron-nitrogen composite material, which comprises the following steps: dissolving a nitrogen-containing ligand and a ferrous salt, heating them to carry out a self-assembly reaction, and obtaining a reaction mixture; removing the solvent from the reaction mixture to obtain a crude iron-containing complex; and drying and calcining the crude iron-containing complex to obtain a carbon-based iron-nitrogen composite material; wherein the nitrogen-containing ligand has a structure shown in the following formula (I):
[0007] In formula (I), m Ra are independently selected from carboxyl or carboxyl-substituted C1-C5 alkyl, and 0≤m≤4; n Rb and n Rb' are independently selected from C6-C 18 Aryl, C5~C 18 The compound is a C1-C5 alkyl radical substituted with a heteroaryl radical, a carboxyl radical or a carboxyl radical, and 0≤n≤3.
[0008] Furthermore, the m Ra are each independently selected from a carboxyl group or a C1-C3 alkyl group substituted with a carboxyl group, and 0≤m≤2; the n Rb and n Rb' are each independently selected from a C6-C 12 Aryl, C5~C 10 Preferably, Ra is selected from carboxyl, and 1≤m≤2; Rb and Rb' are each independently selected from carboxyl or phenyl, and 0≤n≤2; further preferably, the nitrogen-containing ligand is selected from one or more of formula (II), formula (III) and formula (IV),
[0009]
[0010] Furthermore, the molar ratio of the nitrogen-containing ligand to the ferrous salt is (2-4):1; preferably, the ferrous salt is one or more of FeCl2, FeCl2·4H2O and FeSO4·7H2O.
[0011] Furthermore, the solvent is one or more of water, methanol and ethanol; or the solvent is a mixture of chloroform and at least one of methanol and ethanol.
[0012] Furthermore, the temperature of the self-assembly reaction is 50-100° C., and the time is 2-8 hours.
[0013] Furthermore, the drying temperature is 50-100° C., and the drying time is 8-12 hours; preferably, the drying pressure is 80-95 KPa.
[0014] Furthermore, calcination is carried out under a protective gas atmosphere, specifically including: first heating to a calcination temperature at a heating rate of 3 to 5°C / min, and after the calcination is completed, cooling to 20 to 35°C at a cooling rate of 3 to 8°C / min to obtain a carbon-based iron-nitrogen composite material; preferably, the protective gas is nitrogen and / or argon; preferably, the calcination temperature is 500 to 850°C, and the time is 2 to 8h; further preferably, the calcination temperature is 700 to 850°C.
[0015] According to a second aspect of the present invention, a carbon-based iron-nitrogen composite material is further provided. The carbon-based iron-nitrogen composite material is prepared by the above-mentioned method for preparing the carbon-based iron-nitrogen composite material.
[0016] According to the third aspect of the present invention, there is also provided an application of the above carbon-based iron-nitrogen composite material as an active material in a negative electrode sheet of a lithium-ion battery.
[0017] According to a fourth aspect of the present invention, a lithium-ion battery is further provided. The lithium-ion battery comprises a negative electrode, wherein the negative electrode contains a negative electrode active material, and the negative electrode active material is the above-mentioned carbon-based iron-nitrogen composite material.
[0018] The present invention provides a carbon-based iron-nitrogen composite material, a preparation method and application thereof, and a lithium-ion battery. The preparation method uses nitrogen-containing ligands and ferrous salts as raw materials, generates an iron-containing complex through a self-assembly alignment reaction between the two, and then dries and calcines the obtained iron-containing complex to obtain a carbon-based iron-nitrogen composite material. The carbon-based iron-nitrogen composite material obtained after calcining the iron-containing complex prepared according to the above preparation method includes substances of multiple components such as carbon, Fe3C, Fe3N and Fe, and has a layered structure and tubular particles attached to the surface of the layered structure, wherein the tubular particles are hollow structures. The carbon-based iron-nitrogen composite material having the above components and the layered structure and the tubular structure is used in a lithium-ion battery, which can make lithium ions migrate more easily in the lithium-ion battery. The coordination of the above-mentioned specific structure and components can effectively improve the gram capacity and cycle stability of the lithium-ion battery, so that the prepared lithium-ion battery can meet the needs of long-cycle applications. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] The drawings constituting a part of the present application are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the drawings:
[0020] Figure 1 shows a SEM image of the carbon-based iron-nitrogen composite material prepared according to Example 1 of the present invention;
[0021] Figure 2 shows an XRD pattern of the carbon-based iron-nitrogen composite material prepared according to Example 1 of the present invention;
[0022] Figure 3 The XPS graph of the carbon-based iron-nitrogen composite material prepared according to Example 1 of the present invention is shown;
[0023] Figure 4 The graph shows the gram capacity change curve during the cycle of a lithium ion battery using the carbon-based iron-nitrogen composite material prepared in Example 1 of the present invention as the negative electrode active material. DETAILED DESCRIPTION
[0024] It should be noted that, in the absence of conflict, the embodiments and features in the embodiments of the present application can be combined with each other. The present invention will be described in detail below with reference to the accompanying drawings and in combination with the embodiments.
[0025] As described in the background technology section, the theoretical gram capacity of traditional graphite negative electrode materials is 372mAh / g, but its actual gram capacity is low, often below 360mAh / g, and there is a problem of volume expansion during the cycle process, which seriously affects the capacity and cycle stability of the battery, limiting its application in long-cycle batteries. In view of the above problems, it is urgently needed to develop a new type of negative electrode active material, which can not only increase the capacity of lithium-ion batteries, but also have excellent cycle stability performance for lithium-ion batteries to meet the needs of long-cycle applications of lithium-ion batteries.
[0026] In order to solve the above problems, the present invention provides a method for preparing a carbon-based iron-nitrogen composite material, which comprises the following steps: dissolving a nitrogen-containing ligand and a ferrous salt, heating them to carry out a self-assembly reaction, and obtaining a reaction mixture; removing the solvent from the reaction mixture to obtain a crude iron-containing complex; and drying and calcining the crude iron-containing complex to obtain a carbon-based iron-nitrogen composite material; wherein the nitrogen-containing ligand has a structure shown in the following formula (I):
[0027] In formula (I), m Ra are independently selected from carboxyl or carboxyl-substituted C1-C5 alkyl, and 0≤m≤4; n Rb and n Rb' are independently selected from C6-C 18 Aryl, C5~C 18 The compound is a C1-C5 alkyl radical substituted with a heteroaryl radical, a carboxyl radical or a carboxyl radical, and 0≤n≤3.
[0028] In the preparation method of the carbon-based iron-nitrogen composite material provided by the present invention, the nitrogen-containing ligand having the above-mentioned specific structure and the ferrous salt are first mixed and heated to perform a self-assembly coordination reaction to obtain a reaction mixture; then the solvent in the reaction mixture is removed to obtain a crude iron-containing complex; and the obtained crude iron-containing complex is dried and calcined to obtain a carbon-based iron-nitrogen composite material including multiple components such as carbon, Fe3C, Fe3N and Fe. The nitrogen-containing ligand used in the preparation of the carbon-based iron-nitrogen composite material of the present invention has a structure shown in formula (I), and the nitrogen-containing ligand described in formula (I) includes three nitrogen-containing six-membered heterocyclic rings and a benzene ring, wherein the N atoms in the three nitrogen-containing six-membered heterocyclic rings can provide lone electron pairs to form an iron-containing complex having six coordination bonds and two nitrogen-containing ligands with the ferrous ions in the ferrous salt. The benzene ring connected to the nitrogen-containing six-membered heterocyclic ring can form a conjugated structure with the ligand in the system, so that the ligand has a more stable structure. The formed iron-containing complex has a structure shown in the following formula (V):
[0029] In formula (V), m Ra are independently selected from carboxyl or carboxyl-substituted C1-C5 alkyl, and 0≤m≤4; n Rb and n Rb' are independently selected from C6-C 18 Aryl, C5~C 18 The compound is a C1-C5 alkyl radical substituted with a heteroaryl radical, a carboxyl radical or a carboxyl radical, and 0≤n≤3.
[0030] In particular, after a large number of experiments, the inventors creatively discovered that the different substituents on the ligands of the complex will result in obvious differences in the gram capacity and cycle stability of the prepared carbon-based iron-nitrogen composite materials when used in lithium-ion batteries. The substituent Ra on the nitrogen-containing ligand is a carboxyl group or a C1-C5 alkyl group substituted with a carboxyl group. The carboxyl group has the property of withdrawing electrons. The substituent Ra will be connected to the nitrogen-containing six-membered heterocyclic ring through the benzene ring in the ligand structure. The purpose of affecting the electron cloud density between the ligand and the coordinated metal ion can be achieved by regulating the type and number of the substituent Ra. The substituents Rb and Rb' on the nitrogen-containing ligand are each independently selected from C6-C 18 Aryl, C5~C 18 The introduction of heteroaryl, carboxyl or carboxyl substituted C1-C5 alkyl, Rb and Rb' is intended to adjust the electron distribution between the ligand and the metal center and the spatial configuration of the complex through their specific electronic effects (electron withdrawal or electron donation) and stereo effects. The above substituents will affect the electronic effect in the formed iron-containing complex, and then affect the performance of the carbon-based iron-nitrogen composite material after calcination.
[0031] Analyzing the reasons for the above phenomenon, there may be the following aspects: First, the structure of the complex, especially the coordination environment between the coordinated metal ions and the ligands, will affect the structure of the formed carbon-based iron-nitrogen composite material. The carbon-based iron-nitrogen composite material prepared by the preparation method of the present invention includes materials with multiple components of carbon, Fe3C, Fe3N and Fe, and has a layered structure and a tubular particle structure. The complex with a good coordination environment, the synergistic participation of multiple components of carbon, Fe3C, Fe3N and Fe in the carbon-based iron-nitrogen composite material formed after calcination, can make the material form a network structure with unique electronic properties, which is beneficial to improve the conductivity and electronic capacity of the material, promote the rapid transmission of lithium ions in the battery, thereby improving the charge and discharge rate and efficiency, and improving the battery capacity, which is crucial for lithium-ion battery materials. Secondly, the structure of the complex will affect the porosity and pore structure of the formed carbon-based iron-nitrogen composite material, thereby affecting the lithium ion diffusion path. The high porosity and appropriate pore structure of the carbon-based iron-nitrogen composite material can provide more lithium ion insertion / deintercalation points, thereby improving the lithium ion diffusion capacity of the material, which is crucial to improving the capacity and cycle performance of the battery.
[0032] In summary, the carbon-based iron-nitrogen composite material prepared by the preparation method described in the present invention has good electrical conductivity. Using it in lithium-ion batteries has a good effect on improving the capacity and cycle stability of the battery, and can effectively extend the cycle life of the battery.
[0033] In a preferred embodiment, the m Ra are each independently selected from a carboxyl group or a carboxyl-substituted C1-C3 alkyl group, and 0≤m≤2; the n Rb and n Rb' are each independently selected from a C6-C 12 Aryl, C5~C 10 Any one of heteroaryl, carboxyl or C1-C3 alkyl substituted with carboxyl, and 0≤n≤3. By controlling the type and number of substituents Ra, Rb and Rb' on the ligand under the above conditions, the configuration and electron distribution of the complex can be regulated, thereby affecting the structure and electron diffusion capacity of the prepared carbon-based iron-nitrogen composite material, which is beneficial to further improve the cycle stability and gram capacity of the battery material. Preferably, Ra is selected from carboxyl, and 1≤m≤2; Rb and Rb' are each independently selected from carboxyl or phenyl, and 0≤n≤2; the number and type of substituents are controlled within the above preferred range, and the overall performance of the prepared carbon-based iron-nitrogen composite material is better. By way of example but not limitation, the nitrogen-containing ligand is selected from one or more of formula (II), formula (III) and formula (IV),
[0034]
[0035] The nitrogen-containing ligands represented by formula (II), formula (III) and formula (IV) are used to prepare a carbon-based iron-nitrogen composite material, and the obtained carbon-based iron-nitrogen composite material is used in a lithium-ion battery, so that the lithium-ion battery can have good cycle stability and gram capacity.
[0036] It should be noted that the above nitrogen-containing ligands are all known materials in the prior art.
[0037] In a preferred embodiment, the molar ratio of the nitrogen-containing ligand to the ferrous salt is (2-4):1; preferably, the ferrous salt is one or more of FeCl2, FeCl2·4H2O and FeSO4·7H2O. When preparing the iron-containing complex, the molar ratio of the nitrogen-containing ligand to the ferrous salt and the type of the ferrous salt are controlled under the above conditions, which is conducive to the full complexation between the iron ions and the nitrogen-containing ligand, forming a more stable complex structure, and further affecting the performance of the carbon-based iron-nitrogen composite material after calcination.
[0038] In a preferred embodiment, the solvent is one or more of water, methanol and ethanol; or the solvent is a compound of chloroform and at least one of methanol and ethanol. Selecting the above solvents during the self-assembly reaction can make the reactants dissolve better, further increase the reaction rate, and further affect the dispersibility of the carbon-based iron-nitrogen composite material.
[0039] In a preferred embodiment, the temperature of the self-assembly reaction is 50-100°C and the time is 2-8 hours. Controlling the temperature and time of the self-assembly reaction within the above range can make the reaction more complete, help improve the crystallinity and activity of the composite material after calcination, and thus enhance its performance as a negative electrode material.
[0040] In a preferred embodiment, the drying temperature is 50-100°C and the time is 8-12 hours; preferably, the pressure during drying is 80-95KPa. Controlling the drying conditions can effectively remove excess solvent and avoid structural damage of the material caused by residual solvent during the calcination process. Drying under lower pressure can further increase the porosity of the material, which is conducive to better diffusion of lithium ions in the material, thereby further enhancing the overall performance of the battery.
[0041] In a preferred embodiment, calcination is carried out under a protective gas atmosphere, specifically including: first heating to the calcination temperature at a heating rate of 3 to 5 ° C / min, and then cooling to 20 to 35 ° C at a cooling rate of 3 to 8 ° C / min after the calcination is completed, to obtain a carbon-based iron-nitrogen composite material; preferably, the protective gas is nitrogen and / or argon; preferably, the calcination temperature is 500 to 850 ° C, and the time is 2 to 8 hours. High-temperature calcination under the protection of an inert gas (such as nitrogen and argon) can prevent the material from being oxidized at high temperatures and ensure the purity and stability of the product. Controlling the calcination temperature and time within the above range can make the formed iron-containing complex better decompose and carbonize, forming a carbon-based structure with uniform structure and composition, while promoting the combination of metal and nitrogen to form iron nitrogen compounds (Fe3N) and iron carbides (Fe3C). Furthermore, the carbon-based iron-nitrogen composite material can have a better microstructure, further improve its conductivity and lithium ion embedding / deintercalation ability, and enhance the charge and discharge performance and cycle stability of the battery; further preferably, the calcination temperature is 700-850°C, and the calcination temperature is controlled within the above preferred range, the above effect is better.
[0042] According to the second aspect of the present invention, there is also provided a carbon-based iron-nitrogen composite material, which is prepared by the preparation method of the above-mentioned carbon-based iron-nitrogen composite material. The carbon-based iron-nitrogen composite material includes multiple components of carbon, Fe3C, Fe3N and Fe, and has a layered structure and a hollow tubular particle structure. The above-mentioned carbon-based iron-nitrogen composite material is used in a lithium-ion battery. Under the synergistic effect between the various components in the carbon-based iron-nitrogen composite material and the synergistic influence of its structure, the capacity and cycle stability of the lithium-ion battery can be effectively improved, so that the lithium-ion battery can meet the needs of long-term use.
[0043] According to the third aspect of the present invention, there is also provided a use of the carbon-based iron-nitrogen composite material as an active material in a negative electrode sheet of a lithium-ion battery. The prepared carbon-based iron-nitrogen composite material is used as an active material in a negative electrode sheet of a lithium-ion battery, which is beneficial to further improve the cycle stability and battery capacity of the lithium-ion battery.
[0044] According to a fourth aspect of the present invention, a lithium-ion battery is also provided, the lithium-ion battery comprising a negative electrode, the negative electrode containing a negative electrode active material, the negative electrode active material being the above-mentioned carbon-based iron-nitrogen composite material. Applying the carbon-based iron-nitrogen composite material proposed in the present invention as a negative electrode active material to a lithium-ion battery can improve the cycle stability and battery capacity of the lithium-ion battery, and make the lithium-ion battery have a good service life.
[0045] The present application is further described in detail below in conjunction with specific embodiments. These embodiments should not be construed as limiting the scope of protection claimed in the present application.
[0046] It should be further explained here that the nitrogen-containing ligands used in the embodiments of the present invention are mainly nitrogen-containing ligands having structures shown in formula (II), formula (III) and formula (IV):
[0047]
[0048] Example 1
[0049] The nitrogen-containing ligand and FeCl2·4H2O are mixed in a molar ratio of 2:1 and dissolved in a mixed solvent of methanol and chloroform (the volume ratio of methanol and chloroform is 1:1), and heated at 70°C for 3h to perform a self-assembly alignment reaction to obtain a reaction mixture; the solvent in the reaction mixture is removed by rotary evaporation to obtain a crude iron-containing complex. The obtained crude iron-containing complex is first placed in a vacuum drying oven and dried for 12h at a temperature of 60°C and a pressure of 95KPa. Then it is placed in a tubular furnace, heated to 700°C at a heating rate of 4°C / min under an argon protective gas atmosphere, and after calcining for 3h, it is cooled to 25°C at a cooling rate of 3°C / min to obtain the carbon-based iron-nitrogen composite material. Among them, the structure of the nitrogen-containing ligand used in this embodiment is a nitrogen-containing ligand having a structure shown in formula (II).
[0050] The prepared carbon-based iron-nitrogen composite material was tested by scanning electron microscopy (SEM), XRD and XPS, and the results are shown in Figure 1 , Figure 2 and Figure 3 .according to Figure 1 The SEM images in FIG. 2 show that the prepared carbon-based iron-nitrogen composite material has a uniform particle size, and its average particle size is about 100 nm, with a layered structure and hollow tubular particles (see Figure 1 (marked in) structure. Figure 2 From the XRD diagram in Figure 1, it can be seen that the carbon-based iron-nitrogen composite material is composed of carbon, Fe3C, Fe3N and Fe. Figure 3 The XPS graph in further proves that the components of the carbon-based iron-nitrogen composite material include the above components.
[0051] The carbon-based iron-nitrogen composite material prepared as above is used as an active material in the negative electrode plate of a lithium-ion battery.
[0052] Example 2
[0053] The nitrogen-containing ligand and FeCl2·4H2O are mixed in a molar ratio of 2:1 and dissolved in a mixed solvent of methanol and chloroform (the volume ratio of methanol and chloroform is 1:1), and heated at 70°C for 3h to perform a self-assembly alignment reaction to obtain a reaction mixture; the solvent in the reaction mixture is removed by rotary evaporation to obtain a crude iron-containing complex. The obtained crude iron-containing complex is first placed in a vacuum drying oven and dried for 12h at a temperature of 60°C and a pressure of 95KPa. Then it is placed in a tubular furnace, heated to 500°C at a heating rate of 4°C / min under an argon protective gas atmosphere, and after calcining for 6h, it is cooled to 25°C at a cooling rate of 3°C / min to obtain the carbon-based iron-nitrogen composite material. Among them, the structure of the nitrogen-containing ligand used in this embodiment is a nitrogen-containing ligand having a structure shown in formula (II).
[0054] The carbon-based iron-nitrogen composite material prepared as above is used as an active material in the negative electrode plate of a lithium-ion battery.
[0055] Example 3
[0056] The nitrogen-containing ligand and FeCl2·4H2O are mixed in a molar ratio of 2:1 and dissolved in a mixed solvent of methanol and chloroform (the volume ratio of methanol and chloroform is 1:1), and heated at 70°C for 3h to perform a self-assembly alignment reaction to obtain a reaction mixture; the solvent in the reaction mixture is removed by rotary evaporation to obtain a crude iron-containing complex. The obtained crude iron-containing complex is first placed in a vacuum drying oven and dried for 12h at a temperature of 60°C and a pressure of 95KPa. Then it is placed in a tubular furnace, heated to 850°C at a heating rate of 4°C / min under an argon protective gas atmosphere, and after calcining for 3h, it is cooled to 25°C at a cooling rate of 3°C / min to obtain the carbon-based iron-nitrogen composite material. Among them, the structure of the nitrogen-containing ligand used in this embodiment is a nitrogen-containing ligand having a structure shown in formula (II).
[0057] The carbon-based iron-nitrogen composite material prepared as above is used as an active material in the negative electrode plate of a lithium-ion battery.
[0058] Example 4
[0059] The nitrogen-containing ligand and FeSO4·7H2O are mixed in a molar ratio of 2:1 and dissolved in a mixed solvent of methanol and chloroform (the volume ratio of methanol and chloroform is 1:1), and heated at 70°C for 3h to perform a self-assembly alignment reaction to obtain a reaction mixture; the solvent in the reaction mixture is removed by rotary evaporation to obtain a crude iron-containing complex. The obtained crude iron-containing complex is first placed in a vacuum drying oven and dried for 12h at a temperature of 60°C and a pressure of 95KPa. Then it is placed in a tubular furnace, heated to 700°C at a heating rate of 4°C / min under an argon protective gas atmosphere, and after calcining for 3h, it is cooled to 25°C at a cooling rate of 3°C / min to obtain the carbon-based iron-nitrogen composite material. Among them, the structure of the nitrogen-containing ligand used in this embodiment is a nitrogen-containing ligand having a structure shown in formula (II).
[0060] The carbon-based iron-nitrogen composite material prepared as above is used as an active material in the negative electrode plate of a lithium-ion battery.
[0061] Example 5
[0062] The nitrogen-containing ligand and FeSO4·7H2O are mixed in a molar ratio of 2:1 and dissolved in a mixed solvent of methanol and chloroform (the volume ratio of methanol and chloroform is 1:1), and heated at 70°C for 3h to perform a self-assembly alignment reaction to obtain a reaction mixture; the solvent in the reaction mixture is removed by rotary evaporation to obtain a crude iron-containing complex. The obtained crude iron-containing complex is first placed in a vacuum drying oven and dried for 12h at a temperature of 60°C and a pressure of 95KPa. Then it is placed in a tubular furnace, heated to 600°C at a heating rate of 4°C / min under an argon protective gas atmosphere, and after calcining for 4h, it is cooled to 25°C at a cooling rate of 3°C / min to obtain the carbon-based iron-nitrogen composite material. Among them, the structure of the nitrogen-containing ligand used in this embodiment is a nitrogen-containing ligand having a structure shown in formula (II).
[0063] The carbon-based iron-nitrogen composite material prepared as above is used as an active material in the negative electrode plate of a lithium-ion battery.
[0064] Example 6
[0065] The nitrogen-containing ligand and FeCl2 are mixed in a molar ratio of 2:1 and dissolved in a mixed solvent of methanol and chloroform (the volume ratio of methanol to water is 1:1), and heated at 100°C for 2h to perform a self-assembly alignment reaction to obtain a reaction mixture; the solvent in the reaction mixture is removed by rotary evaporation to obtain a crude iron-containing complex. The obtained crude iron-containing complex is first placed in a vacuum drying oven and dried for 12h at a temperature of 50°C and a pressure of 95KPa. Then it is placed in a tubular furnace, heated to 700°C at a heating rate of 3°C / min under an argon protective gas atmosphere, and after calcining for 8h, it is cooled to 35°C at a cooling rate of 8°C / min to obtain the carbon-based iron-nitrogen composite material. Among them, the structure of the nitrogen-containing ligand used in this embodiment is a nitrogen-containing ligand having a structure shown in formula (II).
[0066] The carbon-based iron-nitrogen composite material prepared as above is used as an active material in the negative electrode plate of a lithium-ion battery.
[0067] Example 7
[0068] The nitrogen-containing ligand and FeCl2·4H2O are mixed in a molar ratio of 4:1 and dissolved in a solvent methanol, and heated at 50°C for 8h to perform a self-assembly reaction to obtain a reaction mixture; the solvent in the reaction mixture is removed by rotary evaporation to obtain a crude iron-containing complex. The obtained crude iron-containing complex is first placed in a vacuum drying oven and dried for 8h at a temperature of 100°C and a pressure of 80KPa. Then it is placed in a tubular furnace, heated to 700°C at a heating rate of 5°C / min under an argon protective gas atmosphere, and after calcination for 2h, it is cooled to 20°C at a cooling rate of 3°C / min to obtain the carbon-based iron-nitrogen composite material. Among them, the structure of the nitrogen-containing ligand used in this embodiment is a nitrogen-containing ligand having a structure shown in formula (II).
[0069] The carbon-based iron-nitrogen composite material prepared as above is used as an active material in the negative electrode plate of a lithium-ion battery.
[0070] Example 8
[0071] The difference between Example 8 and Example 1 is that the structure of the nitrogen-containing ligand used in this example is a nitrogen-containing ligand having a structure represented by formula (III).
[0072] Example 9
[0073] The difference between Example 9 and Example 1 is that the structure of the nitrogen-containing ligand used in this example is a nitrogen-containing ligand having a structure represented by formula (IV).
[0074] Example 10
[0075] The difference between Example 10 and Example 1 is that the molar ratio of the nitrogen-containing ligand to the ferrous salt is 1:1, the self-assembly reaction time is 1 h, the temperature is 40° C., and the calcination temperature is 300° C.
[0076] Comparative Example 1
[0077] The difference between Comparative Example 1 and Example 1 is that graphite material (model: Shanshan FSN-1) is used as the active material in the negative electrode plate of the lithium-ion battery.
[0078] Comparative Example 2
[0079] The difference between Comparative Example 1 and Example 1 is that graphite material (model: DY-9B) is used as the active material in the negative electrode sheet of the lithium ion battery.
[0080] Comparative Example 3
[0081] The difference between Comparative Example 3 and Example 1 is that no self-assembly reaction is performed, and the nitrogen-containing ligand and FeCl2·4H2O are directly mixed at a molar ratio of 2:1 and then calcined directly.
[0082] The corresponding active materials in the above examples and comparative examples were used to prepare lithium ion batteries, and the gram capacity and cycle stability of the prepared lithium ion batteries were tested. The results are shown in Table 1.
[0083] Among them, the preparation method of the lithium ion battery includes: using the carbon-based iron-nitrogen composite material prepared by the present invention as the negative electrode active material, mixing it with the conductive agent conductive carbon black (SP) and the binder polyvinylidene fluoride (PVDF) in a mass ratio of 96:1:3 to prepare the negative electrode slurry, and using N-methylpyrrolidone (NMP) as the organic solvent of the negative electrode slurry; coating the prepared negative electrode slurry on the copper foil with a coating thickness of 80μm, and then drying it at 80℃ for 12h under vacuum conditions, and punching the sheet to obtain the negative electrode plate. The positive electrode uses lithium iron phosphate, the diaphragm is a PE film, and the electrolyte is a solution of LiPF6 with a molar concentration of 1mol / L (wherein the solvent is ethylene carbonate (EC), dimethyl carbonate (DMC) and ethyl methyl carbonate (EMC) mixed in a mass ratio of 3:5:2). The positive electrode plate, the negative electrode plate and the battery diaphragm are assembled in the form of a stack, and then the preparation of the lithium ion battery is completed through the steps of assembly, injection, formation and constant volume.
[0084] Gram capacity test method: discharge to 2.5V with 0.1C current, let stand for 10 minutes, charge to 3.65V with 0.1C current, let stand for 10 minutes, discharge to 2.5V with 0.1C current, obtain the discharge capacity, and the ratio of the obtained discharge capacity to the effective weight of the active material is the gram capacity of the battery material.
[0085] 100-cycle cycle retention rate test method: 100 cycles of charge and discharge at 0.33C, the capacity retention rate is the ratio of the discharge capacity in the 100th cycle to the discharge capacity in the first cycle.
[0086] Table 1
[0087] Gram capacity / mAh / g 100-week cycle retention rate % Example 1 400 98% Example 2 378 95% Example 3 400 95% Example 4 394 98% Example 5 385 98% Example 6 405 97% Example 7 402 98% Example 8 395 97% Example 9 390 96% Example 10 365 95% Comparative Example 1 340 95% Comparative Example 2 350 94% Comparative Example 3 200 80%
[0088] From the above description, it can be seen that the above embodiments of the present invention achieve the following technical effects:
[0089] The carbon-based iron-nitrogen composite materials prepared in Example 1 and Example 10 are used as active materials in the negative electrode sheet of a lithium-ion battery to prepare a lithium-ion battery. The gram capacity of the prepared lithium-ion battery can reach 405 mAh / g, and the capacity retention rate after 100 cycles is also above 95%. In particular, in Example 1 to Example 9, the conditions for preparing the carbon-based iron-nitrogen composite materials are controlled within the preferred range, and the lithium-ion battery has not only a good gram capacity, but also a good capacity retention rate, and the comprehensive performance of the lithium-ion battery is better.
[0090] The change in gram capacity of the lithium ion battery prepared in Example 1 during the cycle process is plotted as shown in the figure. Figure 4 According to Figure 4 It can be seen that the discharge capacity in grams in the first week is 400 mAh / g, and the discharge capacity in grams after 100 cycles is 392 mAh / g. The change is not large, and there is no obvious decreasing trend in the capacity in grams. It can be seen that using the carbon-based iron-nitrogen composite material prepared by the present invention as the active material in the negative electrode sheet of a lithium-ion battery can make the lithium-ion battery have a better capacity in grams and at the same time have better cycle stability. It can be seen that the prepared lithium-ion battery can be used for a longer period of time.
[0091] Comparative Examples 1 and 2 use conventional graphite materials as the negative electrode active material in lithium-ion batteries. The cycle stability performance of the prepared lithium-ion batteries and the lithium-ion batteries prepared using carbon-based iron-nitrogen composite materials as the active material in the negative electrode plate of lithium-ion batteries is not much different, but the gram capacity is indeed quite different. Comparative Example 3 is to mix the nitrogen-containing ligand and the ferrous salt, and then directly calcine them without self-assembly reaction, and use the prepared material as the active material in the negative electrode plate of the lithium-ion battery to prepare a lithium-ion battery. Its gram capacity is far different from that in the embodiments of the present invention.
[0092] In summary, the carbon-based iron-nitrogen composite material prepared by the improved preparation method of the present invention has good electrical conductivity. Using it in lithium-ion batteries has a good effect on improving the capacity and cycle stability of lithium-ion batteries, and can make the lithium-ion batteries have a better cycle life.
[0093] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A method for preparing a carbon-based iron-nitrogen composite material, characterized in that: The preparation method comprises the following steps: Dissolving the nitrogen-containing ligand and the ferrous salt, and heating them to carry out a self-assembly reaction to obtain a reaction mixture; removing the solvent from the reaction mixture to obtain a crude iron-containing complex; Drying and calcining the crude iron-containing complex to obtain the carbon-based iron-nitrogen composite material; Wherein, the nitrogen-containing ligand has a structure as shown in the following formula (I): In the formula (I), the m Ra are each independently selected from a carboxyl group or a C1-C5 alkyl group substituted with a carboxyl group, and 0≤m≤4; the n Rb and the n Rb' are each independently selected from a C6-C 18 Aryl, C5~C 18 The compound is a C1-C5 alkyl radical substituted with a heteroaryl radical, a carboxyl radical or a carboxyl radical, and 0≤n≤3.
2. The method for preparing the carbon-based iron-nitrogen composite material according to claim 1, characterized in that: The m Ra are each independently selected from a carboxyl group or a C1-C3 alkyl group substituted with a carboxyl group, and 0≤m≤2; the n Rb and the n Rb' are each independently selected from a C6-C 12 Aryl, C5~C 10 Any one of heteroaryl, carboxyl or C1-C3 alkyl substituted with carboxyl, and 0≤n≤3; Preferably, the Ra is selected from a carboxyl group, and 1≤m≤2; the Rb and the Rb' are each independently selected from a carboxyl group or a phenyl group, and 0≤n≤2; Further preferably, the nitrogen-containing ligand is selected from one or more of formula (II), formula (III) and formula (IV), 3. The method for preparing the carbon-based iron-nitrogen composite material according to claim 1, characterized in that: The molar ratio of the nitrogen-containing ligand to the ferrous salt is (2-4):1; Preferably, the ferrous salt is one or more of FeCl2, FeCl2·4H2O and FeSO4·7H2O.
4. The method for preparing the carbon-based iron-nitrogen composite material according to any one of claims 1 to 3, characterized in that: The solvent is one or more of water, methanol and ethanol; or, the solvent is a mixture of chloroform and at least one of the methanol and ethanol.
5. The method for preparing the carbon-based iron-nitrogen composite material according to any one of claims 1 to 3, characterized in that: The temperature of the self-assembly reaction is 50-100° C. and the time is 2-8 hours.
6. The method for preparing the carbon-based iron-nitrogen composite material according to any one of claims 1 to 3, characterized in that: The drying temperature is 50-100°C and the drying time is 8-12h; Preferably, the pressure during drying is 80-95 KPa.
7. The method for preparing the carbon-based iron-nitrogen composite material according to any one of claims 1 to 3, characterized in that: The calcination is carried out in a protective gas atmosphere, specifically comprising: firstly heating the temperature to a calcination temperature at a heating rate of 3 to 5°C / min, and then cooling the temperature to 20 to 35°C at a cooling rate of 3 to 8°C / min after the calcination is completed, to obtain the carbon-based iron-nitrogen composite material; Preferably, the protective gas is nitrogen and / or argon; Preferably, the calcination temperature is 500-850°C and the time is 2-8h; More preferably, the calcination temperature is 700-850°C.
8. A carbon-based iron-nitrogen composite material, characterized in that: The carbon-based iron-nitrogen composite material is prepared by the method for preparing the carbon-based iron-nitrogen composite material according to any one of claims 1 to 7.
9. Use of the carbon-based iron-nitrogen composite material according to claim 8 as an active material in a negative electrode sheet of a lithium-ion battery.
10. A lithium ion battery comprising a negative electrode, wherein the negative electrode contains a negative electrode active material, characterized in that: The negative electrode active material is the carbon-based iron-nitrogen composite material according to claim 8.
Citation Information
Cited By
Positive electrode material and preparation method thereof, positive plate and lithium ion battery
CN120914233A
Cathode material, preparation method thereof, cathode sheet and lithium ion battery
CN120914233B